Uporedna analiza kliničkih i laboratorijskih parametara pacijenata sa autoimunom i idiopatskom hroničnom urtikarijom - Ninković Baroš, Đuka; Gajanin, Vesna; Zrnić, Bogdan; Gajanin, Živorad; Katalina, Gordana (Scripta Medica, 2021)
Background: According to the cause, chronic urticaria is most frequently divided into autoimmune and idiopathic urticaria. Aim of the paper was to determine the frequency of autoimmune urticaria using autologous serum skin testing and a comparative analysis of chronic idiopathic and chronic autoimmune urticaria by disease course, severity and most common comorbidities.Methods: Analysis covered 64 adult patients of both sexes with chronic urticaria, divided into two groups according to their positivity in autologous serum skin testing (group I with positive test and group II with negative test). General haematological and biochemical parameters, antithyroid antibodies, hepatitis serum markers, Helicobacter pylori and Borrelia burgdorferi antibodies were performed for patients in both groups. First group patients were treated by autologous blood therapy (autohaemotherapy). The analytical statistical tool SPSS (Statistical Product and Service Solutions) version 20 for descriptive statistics and statistical methods was used. The significance level used was p = 0.05.Results: The frequency of positive autologous serum test in total population of patients with chronic urticaria was 43.8 %. The average duration of urticaria was 20 months in both groups. Statistically significant difference was found in weekly scores between the studied groups (p = 0.032) in favour of chronic autoimmune urticaria with a positive autologous serum test. Subjects with chronic autoimmune urticaria had a significantly higher association with autoimmune thyroid diseases.Conclusions: Direct relation was established between the use of autologous blood therapy in patients with autoimmune chronic urticaria and improvement of the clinical picture.